Applications of Linear Programming For Profit Maximization In Food Industry - Abdul Rizal, Nurul Syafika; Mohd Razali, Dr Siti Noor Asyikin (Enhanced Knowledge in Sciences and Technology, 2023)
Food has become a pivotal part of our daily lives. The linear programming method is commonly used in the food industry, such as developing linear programming model for food products. The purpose of this study was to create a mathematical linear programming model for two datasets of food types and to determine the optimal profit for each food type in order to maximise profit for the food industry. The last objective is to analyse the flexibility of the linear programming model using sensitivity analysis and visualise the result using descriptive analysis. Two data sets involves are ABC Fruit Stall located at Sungai Kob (case study 1) and the Bakery Shop at Kulim (case study 2). The result of Linear Programming model shows that the ABC company (case study 1) will gain profit RM 276.77 per day. While, for the Bakery Shop (case study 2), the result shows that the optimal profit is RM 370.50 per week. For sensitivity analysis, case study 1 shows that if the quantity supply of wafers and flavour is increased, it will contribute increment profit of about 14.68% and 10.00% respectively to the ABC Stall. While the sensitivity analysis for case study 2 shows that increasing supply of sugar contributes approximately 14.78% increase in profit to the bakery shop. For future study, it is recommended to obtain large datasets from related authorities and others food industries.